1998
DOI: 10.1017/s0376892998000423
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of common lands to household economies in Haryana, India

Abstract: Common lands, being a significant form of natural resource endowment in many developing countries, play a vital role in maintaining the ecological balance, and more particularly in supporting the people, especially the rural poor, in eking out their livelihood. However, the contributions of common lands to the rural economy and ecology have remained unappreciated which has led to the depletion and degradation of these lands. In an attempt to examine the nature and extent of contribution of common lands to hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In southern Africa, it has been shown that poorer households tend to opportunistically invest in activities with few entry barriers, such as the collection of forest products, and EI contributes more to the total incomes of the poor (Campbell et al, 2000;Fisher, 2004;Shackleton andShackleton, 2004, 2006a,b;Shackleton et al, 2007Shackleton et al, , 2008. Similar observations linking poor households with greater dependence are revealed in South America, for example around Peru's Pacaya-Samiria reserve (Takasaki et al, 2001), and in India by Qureshi and Kumar's (1998) extensive studies, prompting the latter to reiterate that the maintenance of common areas where the poor can derive livelihoods is "absolutely crucial". Table 3 shows that the households involved in collecting park resources had significantly lower NPEI despite their high EI.…”
Section: Household Characteristics and Park Environmental Incomementioning
confidence: 68%
“…In southern Africa, it has been shown that poorer households tend to opportunistically invest in activities with few entry barriers, such as the collection of forest products, and EI contributes more to the total incomes of the poor (Campbell et al, 2000;Fisher, 2004;Shackleton andShackleton, 2004, 2006a,b;Shackleton et al, 2007Shackleton et al, , 2008. Similar observations linking poor households with greater dependence are revealed in South America, for example around Peru's Pacaya-Samiria reserve (Takasaki et al, 2001), and in India by Qureshi and Kumar's (1998) extensive studies, prompting the latter to reiterate that the maintenance of common areas where the poor can derive livelihoods is "absolutely crucial". Table 3 shows that the households involved in collecting park resources had significantly lower NPEI despite their high EI.…”
Section: Household Characteristics and Park Environmental Incomementioning
confidence: 68%
“…Although relatively little work in South Africa has specifically disaggregated resource use and income data based on socio-economic characteristics, there are clear indicators that poorer and more isolated communities, as well as households that are less well off or headed by women, are often more dependent on the natural resource base (Shackleton et al, 2002a;Shackleton and Shackleton, 2006). This finding is not unusual and a significant number of studies across the tropics have demonstrated that it is generally the poorest households who are most directly reliant on nontimber forest products (NTFPs) for both subsistence and cash income (Clarke et al, 1996;Campbell et al, 1997;Qureshi and Kumar, 1998;Cavendish, 2000;Neumann and Hirsch, 2000;Cavendish, 2002). Similarly, a number of studies have indicated that among households headed by women forest resources often contribute significantly more to total household income than is the case for households headed by men (Clarke et al, 1996;Cavendish, 2000).…”
Section: Supply Of Basic Needsmentioning
confidence: 99%
“…On the other hand, Adhikari (2003), based on data from 330 households in 8 "forest user groups" in Nepal, finds that dependence increases with income, from 14% for the poor to 22% for the rich. 5 All four studies also examine the relationship between income and the absolute level of resource use, 1 Other, much smaller-scale studies include Pasha (1992), Singh, Singh and Singh (1996), Nadkarni (1997), Qureshi and Kumar (1998), Beck and Ghosh (2000), and Fisher (2004). 2 Although we refer to households with incomes at the higher end of the rural income distribution here, and elsewhere in the paper, as rich, it is important to note that these households are still poor in absolute terms.…”
Section: Introductionmentioning
confidence: 99%